Seed-borne fungi of herbs cultivated in South Africa and evaluation of non-chemical seed treatments to control Alternaria sp. on coriander - Aveling, Terry A.S. (University of Pretoria, 2022)
Dissertation (MSc (Plant Pathology))--University of Pretoria, 2015.